2005
DOI: 10.1124/mol.104.002725
|View full text |Cite
|
Sign up to set email alerts
|

Elastin Peptides Activate Extracellular Signal-Regulated Kinase 1/2 via a Ras-Independent Mechanism Requiring Both p110γ/Raf-1 and Protein Kinase A/B-Raf Signaling in Human Skin Fibroblasts

Abstract: Elastin peptides (EPs) produced during cancer progression bind to the elastin binding protein (EBP) found at the surface of dermal fibroblasts, leading to the expression of collagenase-1 gene. The production of this enzyme involved in stromal reaction is caused by the sustained activation of the extracellular signal-regulated kinases 1/2 (ERK1/2) pathway via cAMP/protein kinase A (PKA) and phosphatidylinositol 3-kinase (PI3K). However, the mechanism of these signaling events remains unknown. We show that -elas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
41
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 39 publications
4
41
0
Order By: Relevance
“…Up to now, EPs were only involved in up-regulation of signaling cascade and gene expression (28,55,56). Thus, biological effects exerted by EPs should take into account the cell type used (37,57), the signaling pathway analyzed (31,56), and, as delineated in this study, the presence or not of coeffectors. As a matter of fact, most of the effects of EPs have been previously investigated using resting cells.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Up to now, EPs were only involved in up-regulation of signaling cascade and gene expression (28,55,56). Thus, biological effects exerted by EPs should take into account the cell type used (37,57), the signaling pathway analyzed (31,56), and, as delineated in this study, the presence or not of coeffectors. As a matter of fact, most of the effects of EPs have been previously investigated using resting cells.…”
Section: Discussionmentioning
confidence: 77%
“…For instance, activation of protein kinase G, cAMP, or cGMP by EPs was reported to induce chemotaxis of monocytes (28 -30). Besides, activation of pertussis toxin-sensitive G proteins and MEK/ERK signaling cascade were involved in EP-mediated effects on cell proliferation as observed in arterial smooth muscle cells and fibroblasts (31,32). In turn, S-gal occupancy by EPs led to the activation of both NF-B and p38 in melanoma cells (33).…”
mentioning
confidence: 96%
“…In human dermal fibroblasts, EDPs upregulate collagenase-1 expression through PKA, PI3K, and ERK1/2 pathway activation [24]. They further demonstrated that κE activates ERK1/2 via a Ras-independent mechanism involving p110γ/Raf-1/MEK1/2 and PKA/B-Raf/ MEK1/2 cascades [10]. Our study demonstrated that EDPs activated ERK and NF-κB signaling pathways in human LF cells ( Figure 5).…”
Section: Discussionmentioning
confidence: 71%
“…In elastin-rich tissues such as artery, lung, and skin, inflammation is concomitant with elastolysis, leading to EDPs generation [10,13,14]. In those pathologies, a direct relationship between inflammation and EDP levels has been established.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation